The Religiosity, Nationality, and Sociality of Pancasila: Toward Pancasila through Soekarno’s Way - Yudi Latif (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2018)
Pancasila is the five principles of the Indonesian state’s philosophical foundation. Its existence reflects the characteristics of Indonesia as a multicultural nation-state, one which has to absorb and transform all elements of the nation into a strong, permanent foundation, and a dynamic guiding principle. The five principles are viewed as the crystalisation of the core values and ideals of the nation, as idealised by the existing “trilogy ideology”: religious ideologies, nationalist ideologies and socialist ideologies. All of the ideologies had been synthesized in order to find a common ground that realises the common good (al-maṣlaḥah al-‘āmmah) for the life of the nation. The history of the conceptualisation of Pancasila had been a long process featuring the “seeding” phase, “formulation” phase, and “commencement” phase. Each phase involves the participation of various actors and elements. However, in a joint work of the nation, one of the most prominent actors is Soekarno. To understand Pancasila, one needs to understand his life and thoughts.DOI: 10.15408/sdi.v25i2.7502